Teacher's strategies in teaching reading narrative text for the tenth graders - Hasanah, Maulidiyah; Ni’mah, Fauziyatun (Jurnal Langua, 2024)
Reading is an important ability that must be learned by students. The students will get knowledge from what they read and can increase language acquisition. The goals of this study are to find out the strategies used by the English teacher in teaching reading narrative text and to find out the student’s responses to the strategies used by the English teacher in teaching reading narrative text for the tenth graders of MA Ihyaul Ulum Cangaan. The study design is descriptive qualitative. Data collection methods include; observation, questionnaire, and documentation. The data analyzed were into three parts; Data Reduction, Data display, and Drawing Conclusions or verifying. This study will focus on the English teacher and 27 tenth-grade students at MA Ihyaul Ulum Cangaan. The result showed that the English teacher employed specific techniques, such as, defining the purpose of reading, silent reading, QAR, analyzing the vocabulary, and discussion strategies. Applying these techniques, the English teacher can utilize a variety of techniques and establish new ways of teaching reading based on the subject. As a result, the teaching of reading techniques became more engaging and successful in improving students’ ability to read narrative text.